Integrated Simulation and Field Analysis of a 48 V Mild-Hybrid Urban Bus: KSG Active-Mode Modeling and Active-Passive Performance Comparison - Picak Adas, Aysima; Aycicek, Engin (MDPI, 2026)
This study presents a real-world performance assessment of a 48 V mild-hybrid urban bus equipped with a crankshaft starter-generator (CSG, denoted as KSG in German terminology), together with model-based validation for KSG Active operation. The 17.8-ton Euro VI test vehicle uses a 160 F supercapacitor module operated within a 38-52 V DC/DC converter voltage window (approximate to 40 Wh usable) to buffer transient high-power events in stop-and-go duty. A controlled A/B comparison (KSG Active vs. KSG Passive) was performed using repeated 0-50-0 km/h launch cycles (15 test cycles per mode). Vehicle CAN signals were recorded using a datalogger and analyzed in Vector vSignalyzer 19.0. Field results show a 17.1% reduction in fuel consumption (32.21 to 26.70 L/100 km) and a 30.4% reduction in time-averaged ICE power demand (58.90 to 40.99 kW). A MATLAB/Simulink R2020a longitudinal dynamics digital twin was developed and validated for the KSG Active mode only against 20 Hz CAN measurements, achieving NRMSE below 5% for key variables. The findings should be interpreted as a controlled same-vehicle comparison under repeatable test-track conditions rather than as a certification-grade fleet-level benchmark.
Keywords: 48 V mild-hybrid system; crankshaft starter-generator; supercapacitor; fuel consumption reduction; dynamic modeling; real-world driving cycle; FUEL CONSUMPTION; EMISSIONS; Energy & Fuels